Graças a Deus, tudo é mistério : a religiosidade como regionalidade em Sagarana, de Guimarães Rosa - Teixeira, Jorgemar (My University, 2017)
This master’s thesis analyzes short stories of Sagarana, written by João Guimarães Rosa, from the perspective of religiosity and regionality. It aims to demonstrate how religiosity contributes to the construction of the characters, the ambience and the plot, revealing traces of the regionality of the Brazilian countryside known as “sertão”. The culture of the “sertão” imagined by Guimarães Rosa is connected to the elements of the religious culture, so that the religiosity comes out of the most different circumstances in the work. In the nine short stories of Rosa's first book, the religiosity erupts in the collective imaginary. This can be observed in places and people’s names, superstitions, rituals, popular festivals and mentions of God and saints found in Sagarana. Thus, religiosity becomes one of the cultural components that best contributes to the composition of the regionality represented in the work, because it dialogues directly with the local beliefs and traditions, using the emotional aspects that often act as a force of the characters and maintain the dynamicity of the plots. During the analysis, the observations of this research are based on studies of literature, culture, regionality and religiosity. It is believed that religiosity, as a cultural manifestation, favors the structuring of the ambience of the “sertão” in Guimarães Rosa’s fiction and the way in which the characters deal with religiosity collaborates to substantiate the cultural field represented in the work.
Este trabalho analisa os contos de Sagarana, de João Guimarães Rosa, sob a perspectiva da religiosidade e da regionalidade. Pretende-se demonstrar como a religiosidade contribui para a construção dos personagens, do ambiente, do enredo, revelando traços da regionalidade sertaneja. A cultura do sertão rosiano está de tal forma imbricada nos elementos da cultura religiosa, que a religiosidade sertaneja emerge das mais distintas circunstâncias na obra. Seja por nomes de lugares e pessoas, seja por superstições e rituais, festas populares e abundantes menções a Deus e aos santos, a religiosidade irrompe no imaginário coletivo dos nove contos do primeiro livro de Rosa. Assim, a religiosidade torna-se um dos componentes culturais que mais contribuem para a composição da regionalidade ali representada, pois dialoga diretamente com as crenças e tradições locais, recorrendo aos aspectos emocionais que muitas vezes atuam como força motriz dos personagens e mantêm a dinamicidade dos enredos. No decorrer das análises, as observações deste trabalho fundamentam-se nos estudos de literatura, cultura, regionalidade e religiosidade. Sustenta-se que a religiosidade, como manifestação cultural, favorece a estruturação do ambiente sertanejo na ficção de Guimarães Rosa e que o modo característico de o sertanejo lidar com a religiosidade colabora para fundamentar o espaço cultural representado na obra.
Keywords: Rosa, João Guimarães, 1908-1967. - Sagarana - Crítica e interpretação; Literatura brasileira - História e crítica; Análise do discurso literário; Religiosidade; Cultura; Rosa, João Guimarães, 1908-1967 - Sagarana - Criticism and interpretation; Brazilian literature - History and criticism; Discourse analysis, Literary; Religiousness; Culture